Cigarette smoke promotes oral leukoplakia via regulating glutamine metabolism and M2 polarization of macrophage - Yanan Zhu; Shuo Zhang; Jiahui Sun; Tingting Wang; Qin Liu; Guanxi Wu; Yajie Qian; Weidong Yang; Yong Wang; Wenmei Wang (Nature Publishing Group, 2021)
Abstract Oral immunosuppression caused by smoking creates a microenvironment to promote the occurrence and development of oral mucosa precancerous lesions. This study aimed to investigate the role of metabolism and macrophage polarization in cigarette-promoting oral leukoplakia. The effects of cigarette smoke extract (CSE) on macrophage polarization and metabolism were studied in vivo and in vitro. The polarity of macrophages was detected by flow cytometric analysis and qPCR. Liquid chromatography-mass spectrometry (LC-MS) was used to perform a metabolomic analysis of Raw cells stimulated with CSE. Immunofluorescence and flow cytometry were used to detect the polarity of macrophages in the condition of glutamine abundance and deficiency. Cell Counting Kit-8 (CCK-8), wound-healing assay, and Annexin V-FITC (fluorescein isothiocyanate)/PI (propidium iodide) double-staining flow cytometry were applied to detect the growth and transferability and apoptosis of Leuk-1 cells in the supernatant of Raw cells which were stimulated with CSE, glutamine abundance and deficiency. Hyperkeratosis and dysplasia of the epithelium were evident in smoking mice. M2 macrophages increased under CSE stimulation in vivo and in vitro. In total, 162 types of metabolites were detected in the CSE group. The metabolites of nicotine, glutamate, arachidic acid, and arginine changed significantly. The significant enrichment pathways were also selected, including nicotine addiction, glutamine and glutamate metabolism, and arginine biosynthesis. The results also showed that the supernatant of Raw cells stimulated by CSE could induce excessive proliferation of Leuk-1 and inhibit apoptosis. Glutamine abundance can facilitate this process. Cigarette smoke promotes oral leukoplakia via regulating glutamine metabolism and macrophage M2 polarization.